Phytogeographic divisions, climate change and plant dieback along the coastal desert of northern Chile - Schulz, Natalie; Aceituno, Patricio; Richter, Michael (ERDKUNDE, 2011)
Along the hyper-arid Chilean coastal desert between 30°S and 18°S the Loma vegetation undergoes a gradual transition from open shrubland to small isolated areas of a scarce plant cover. Floristic and physiognomic features allow a differentiation of five Loma formations, each of them characterized by a distinctive spectrum of plant communities. However, particularly in the northern section of the investigation area, numerous indications point to a strong vegetation decline including a deterioration of plant cover, reduction of the vitality of various taxa, probably also a local loss of some perennial species, and even a dieback of specific populations. These signs of a retrogression, which coincide with a regional disappearance of Guanaco herds in the coastal area between 20°S and 23°30’S, became apparent in the second half of the past century and were most likely provoked by recent climate change in the arid coastal region. Especially the decrease of rainfall frequency might have negative implications for the regeneration and preservation of plants. In addition, a strong reduction of cloudiness in the northernmost section affects plant growth due to further limitations in the water disposability. A projected sustained decline of rainfall is expected to continue endangering the surprisingly high floristic diversity of the sensitive ecosystem complexes in the coastal desert.